PENGARUH MOTIVASI, PERSEPSI KONSUMEN, GAYA HIDUP DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE - Sundari, Siti (LPPM IAIT, 2025)
The purpose of this research was to determine the effect of motivation, consumer perceptions, lifestyle and beliefs on purchasing decisions on Shopee marketplace users in Tasikmalaya City. The sample of this research amounted to 100 respondents. This research uses cluster sampling technique. The data analysis used is quantitative with multiple linier regression method. The results showed that (1) Motivation had a positive and significant effect on purchasing decisions in the shopee marketplace, (2) costumer perceptions had no positive and insignificant, effect on purchasing decisions in the shpee marketplace (3) lifestyle had no positive and insignificant effect on purchasing decisions in the shopee marketplace (4) trust has a positive and significant effect on purchasing decisions in the shopee marketplace (5) motivation, costumer perceptions, lifestyle and trust have a positive and significant impact on purchasing decisions in the shopee marketplace.